Effect of Body Mass Index on Outcomes of Peritoneal Dialysis Patients in India. Issue 4 (June 2014) - Prasad, Narayan; Sinha, Archana; Gupta, Amit; Sharma, Raj Kumar; Bhadauria, Dharmendra; Chandra, Abhilash; Prasad, Kashi Nath; Kaul, Anupama
Objectives: We studied the effect of body mass index (BMI) at peritoneal dialysis (PD) initiation on patient and technique survival and on peritonitis during follow-up. Methods: We followed 328 incident patients on PD (176 with diabetes; 242 men; mean age: 52.6 ± 12.6 years; mean BMI: 21.9 ± 3.8 kg/m 2 ) for 20.0 ± 14.3 months. Patients were categorized into four BMI groups: obese, ≥25 kg/m 2 ; overweight, 23 – 24.9 kg/m 2 ; normal, 18.5 – 22.9 kg/m 2 (reference category); and underweight, <18.5 kg/m 2 . The outcomes of interest were compared between the groups. Results: Of the 328 patients, 47 (14.3%) were underweight, 171 (52.1%) were normal weight, 53 (16.2%) were overweight, and 57 (17.4%) were obese at commencement of PD therapy. The crude hazard ratio (HR) for mortality ( p = 0.004) and the HR adjusted for age, subjective global assessment, comorbidities, albumin, diabetes, and residual glomerular filtration rate ( p = 0.02) were both significantly greater in the underweight group than in the normal-weight group. In comparison with the reference category, the HR for mortality was significantly greater for underweight PD patients with diabetes [2.7; 95% confidence interval (CI): 1.5 to 5.0; p = 0.002], but similar for all BMI categories of nondiabetic PD patients. Median patient survival was statistically inferior in underweight patients than in patients having a normal BMI. Median patient survival in underweight, normal, overweight, and obese patients was, respectively, 26 patient–months (95% CI: 20.9 to 31.0 patient–months), 50 patient–months (95% CI: 33.6 to 66.4 patient–months), 57.7 patient–months (95% CI: 33.2 to 82.2 patient–months), and 49 patient–months (95% CI: 18.4 to 79.6 patient–months; p = 0.015). Death-censored technique survival was statistically similar in all BMI categories. In comparison with the reference category, the odds ratio for peritonitis occurrence was 1.8 (95% CI: 0.9 to 3.4; p = 0.086) for underweight patients; 1.7 (95% CI: 0.9 to 3.2; p = 0.091) for overweight patients; and 3.4 (95% CI: 1.8 to 6.4; p < 0.001) for obese patients. Conclusions: In our PD patients, mean BMI was within the normal range. The HR for mortality was significantly greater for underweight diabetic PD patients than for patients in the reference category. Death-censored technique survival was similar in all BMI categories. Obese patients had a greater risk of peritonitis.